EFFECTS OF DIFFERENT SUPPLEMENTS INCLUSION OF THE ENRICHED DIET ON PRODUCTIVE PERFORMANCE AND EGG STRUCTURE - Natasha Trajan Gjorgovska; Kiril Filev; Vesna Levkov; Rodne Nastova; Vasil Kostov; Srekjko Gjorgjievski; Svetlana Grigorova (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2016)
Nutritional manipulation and genetic selection for egg size and production may lead to changes in egg components. This experiment was carried out to analyze the egg structure parameters of eggs produced by Hisex Brown laying hens fed with diet with different supplements inclusion. The intensity of egg production was significantly higher in the groups fed with enriched feed with iodine (90.00%), vitamin E (90.00%) and selenium (91.98%), and significantly lower in the group fed with DHA inclusion feed (76.00%) in respect to the control group (82.00%), confidence interval of 95%. Concerning diet supplemented with selenium and diet supplemented with vitamin E, the egg yolk weight was statistically different compared with the control group (confidence interval of 95%). The yolk weight averaged 1.80 g and 1.29 g more than yolk weight in the control eggs, respectively. The egg shell weight was statistically different in diet enriched with iodine compared with the control. The egg shell weight averaged 1.48 g less per egg for the eggs enriched with iodine with 17.45% less underweight than the control eggs. Enriched eggs offer consumer a variety of value-added options for their egg purchase. Although enriched eggs may provide consumers with a specific quality attribute or healthful ingredient, they do not appear to provide quality and value in a traditional sense as defined by the standards of quality and grade.